Das Verhältnis von Kapitalmarkt- und Gesellschaftsrecht am Beispiel der Ad-hoc-Publizität bei Compliance-Sachverhalten - Krötz, Kilian (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
The relationship between European insider trading law and German stock corporation law has reached a preliminary climax with the jurisprudence of the CJEU in the "Geltl/Daimler" case. The question of when the obligation to disclose insider information applies to various group-affiliated issuers in the event of compliance violations has once again brought this relationship into prominent focus ever since the rise of the "emissions scandal" in the automotive industry. In this context, the paper examines the intersection between ad hoc disclosure obligations and compliance responsibilities. The investigation which is marked by the purpose of the Market Abuse Regulation, reveals the predominance of European law over national German law.